Preparing Indium Films and Studying the Effect Oxidation on Their Properties - محمد حسين; Seham H. Salman (Ibn Al-Haitham Journal for Pure and Applied Sciences)
This research dealt with the preparation and study of the properties of (In 2O3) as a film. Indium films were used by the vacuum thermal evaporation technique on a glass base, and then these films were thermally treated at a temperature of 300 in the presence of oxygen for some time (30, 60, 90, 120) minutes to obtain films. Through X-ray diffraction examinations, atomic force microscopy, and ultraviolet radiation, the thin, transparent indium films revealed that the prepared films are cubic crystalline semiconducting materials. The dominant orientation of this crystal is 222, and the energy gap ranges between 2.1 and 2.7 eV. It can be prepared in the form of a film and varies with the oxidation times and depends on the surface roughness and the root mean square of the roughness. The grain size depends on the oxidation period with constant temperature and oxygen pumping rate, as is clear from the atomic force microscope images attached to the research.